Child welfare as the primary direction of improving the legislation of the Republic of Kazakhstan: prevention of bullying in everyday and educational life - Ilyassova, G.A.; Zhamburbayeva, S. (Bulletin of the Karaganda University “Law Series”, 2024)
The article is devoted to the actual problem of bullying, that is, intentional and systematic infliction of emo-tional and physical harm to a minor by peers or adults. Despite a number of positive changes provoked by the adoption of appropriate legislative instruments to combat this phenomenon, there are still gaps that need to be addressed in the near future. The need to create a healthy atmosphere is justified by the fact that the well-being of children, the future generation of the Republic of Kazakhstan, is the benchmark for the development and progress of our country. Thus, in this article, the authors analyze the forms and consequences of bullying, world-class statistical indicators, and also study international and national experience in combating this phe-nomenon. Special attention is paid to the role of legislation in ensuring the well-being of the child and pro-tecting him from bullying. The authors propose a number of practical recommendations for improving the legislation of the Republic of Kazakhstan in this area, as well as for improving the legal consciousness and legal culture of the population. The article is of undeniable interest to lawyers, educators, psychologists, soci-ologists, human rights defenders and all those who deal with issues of childhood and child welfare in order to improve the atmosphere prevailing around a minor citizen of our country.